ASEAN Science Leadership Program gets extensive media coverage in Vietnam - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
On 2-5 December 2019, selected scientists from ASEAN countries were invited to attend the ASEAN Science Leadership Program held in Hanoi, Vietnam. The programme was organized by the ASEAN Young Scientist Network which was attended by scientists from Malaysia, Indonesia, Myanmar, Thailand, Laos, the Philippines, Singapore and Vietnam. Malaysian scientists were represented by Assoc. Prof. Dr. Siti Norasmah Hj. Surip (UiTM), Chm. Dr. Shahrul Nizam Ahmad (UiTM), Dr. Siti Hamimah Sheikh Abdul Kadir (UiTM), Assoc. Prof. Dr. Siti Sarah Othman (UPM), Dr. Mas Jaffri Masarudin (UPM), Dr. Thaigarajan Parumasivam (USM) and Assoc. Prof. Dr. Wan Iryani Wan Ismail (UMT). The 4-day programme was filled with various activities to enhance research creativity in their respective fields, enhance collaboration networks between ASEAN scientists and attend the ASEAN Conference for Young Scientists at a newly opened university, Phenikaa University. The inaugural programme had received extensive coverage in the Vietnamese mass media and electronic media.